EVALUASI SARANA DAN PRASARANA PARIWISATA PANTAI PASIR PUTIH DESA LAMREH KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Riki Kurniawan; Renni Anggraini; Irin Caisarina (Prodi Magister Teknik Sipil Unsyiah, 2019)
Pasir Putih Beach located in Lamreh Village is a unique and distinctive tourist attraction which differs from the beaches in other regions. The existence of this beach has not been balanced with the availability of adequate facilities and infrastructure, to provide comfort and activity for tourists. The physical potential found on Pasir Putih Beach is the unique white sand with treesgrowing in the water, calm waves, existing local traditional fishing boat bases, photogenic spots, places which often used as camping sites and barbecues, it is far from the city noise, and close to other tourist objects such as Bukit Suharto Peak, Bukit Lamreh, and Ujung Kelindu. The non-physical potential found in Pasir Putih Beach is the friendly attitude, and the culture of the community. This study aims to identify existing conditions of tourism facilities and infrastructure in Pasir Putih Beach, the level of community participation in tourism development, and to identify strategies for developing tourism facilities and infrastructure. Primary data is obtained through the distribution of questionnaires, observations and interviews. Data analysis used descriptive analysis and SWOT. The results showed that the tourism facilities and infrastructure in Pasir Putih Beach were mostly in accordance with 12 indicators (52.17%). In the development of Pasir Putih Beach tourism, the level of community participation is still low, 72.95% of the community has never participated. The strategy for the development of tourism facilities and infrastructure in Pasir Putih Beach is to increase the quantity and quality of facilities and infrastructure, increase community participation/involvement in facilities and infrastructure maintenance activities, implement legal products in the development of facilities and infrastructure, and form partnerships that can strengthen collaboration in developing the infrastructure.